2021
DOI: 10.1021/acs.energyfuels.0c04247
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Effect of Rock Wettability from Residual Oil on Foam Generation and Propagation in Porous Media

Abstract: One of the common challenges of applying foam for enhanced oil recovery is the foam instability in the presence of crude oil and nonwater-wet surfaces. In this experimental study, we systematically distinguish the effect of rock surface wettability from that of crude oil saturation on foam rheology under reservoir conditions. Neutral-wet Berea and reservoir sandstone cores are prepared by aging with crude oil, followed by the wettability index measurements. Transient foam generation and steady-state foam quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Fannir et al [35] studied the experimental research on two-phase flow displacement using Magnetic Resonance Imaging (MRI) techniques and investided the process of the phase trapping, the front deformation and the phases saturation propagation along a vertical model during (water-oil) two-phase flow. Yadali Jamaloei et al [36][37][38] analyzed the effect of wettability on the microscopic oil displacement mechanism. Alyafei et al [39] took cores containing oil and a specified initial water saturation, injected water flooding until 10 pore volumes, and observed the relationship between the initial oil saturation and the residual saturation.…”
Section: Nomenclaturementioning
confidence: 99%
“…Fannir et al [35] studied the experimental research on two-phase flow displacement using Magnetic Resonance Imaging (MRI) techniques and investided the process of the phase trapping, the front deformation and the phases saturation propagation along a vertical model during (water-oil) two-phase flow. Yadali Jamaloei et al [36][37][38] analyzed the effect of wettability on the microscopic oil displacement mechanism. Alyafei et al [39] took cores containing oil and a specified initial water saturation, injected water flooding until 10 pore volumes, and observed the relationship between the initial oil saturation and the residual saturation.…”
Section: Nomenclaturementioning
confidence: 99%
“…Permeability contrast defined as the ratio of the permeabilities of the fracture and matrix is another key parameter that significantly impacts the performance of foams among a large number of reservoir conditions such as rock wettability, surface roughness, and mineralogy. Such investigations help identify superior chemicals or blends of chemicals for field applications and mitigate the risk by determining, for instance, the optimum range of surfactant concentrations at which a desirable foam performance is achieved for a given fractured medium.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the foam strength in porous media is largely influenced by the surfactant type and concentration, reservoir property (salinity, hardness, temperature, wettability, oil saturation, permeability, heterogeneity, etc. ), operational methods (flow rate, injection scheme, foam quality, etc. ), , gas type, local capillary pressure, and foam texture. Note that the foam steady state may indicate a balance between the lamellae creation rate and lamellae coalescence rate.…”
Section: Introductionmentioning
confidence: 99%
“…It is universally accepted that oil has a detrimental effect on the foam stability, especially when the oil sample contains a large amount of light components. ,, The destabilization effect of oil on the foam stability has been extensively investigated, and several criteria have been proposed to predict the stability of foam in the presence of oil. Among them, the most reliable theory may be based on the stability of the pseudoemulsion film, i.e., the pseudoemulsion film disjoining pressure. , The other theories to account for the oil destabilization effect include lamellae number and the entering/spreading/bridging coefficients, which are calculated based on the surface/interfacial tension .…”
Section: Introductionmentioning
confidence: 99%